Variasi Ketahanan Terhadap Penyakit karat Tumor pada Sengon Tingkat Semai - Liliana Baskorowati; Siti Husna Nurrohmah (Jurnal Pemuliaan Tanaman Hutan, 2011)
The most seriouse affecting Sengon (Sengon (Falcataria moluccana) plantation is Gall rust is coused by the fungus Uromycladium tepperianum (Sacc.) McAlp. This disease reduced the yield due to mortality and stems brakage (fllowing the formation of stem-girdling galls) reduced marketability and  decreased of ghrowth rates. This research aimed to select seedlings sengon which is tolerant to gall rust disease at provenence level, Five seed sources were used for this study i.e. from Papua (Elaigama Hubikosi and Siba Hubikosi) and Java (Candiroto, Kediri and Wonosobo). Inoculation was carried using fresh spora of Uromycladium tepperianum, There times when the seedlingreaches two weeks old. Then obsevation has been done for height and symptom scoring for evaluating disease incidence and severity. The result showed there were variations for height, disease incidence and disease severity. Seedlings sengon from Papua exhibited growth (height) about 6,5-12,2 cm,  and seedlings from Java. It recorded that seedlings from Papua exhibited 0% of disease incidence ansd disease severity, meanwhile seedling from java is more susceptible to the gall rust, by which exhibited hight value of disease incidence (86-94 %0 and disease severity (53-60%).